Serum JAK/STAT profile is related to the IL expression but not with the outcome in pancreatic adenocarcinoma patients - Petrusel, Livia; Ilies, Maria; Leucuta, Daniel; Rusu, Ioana; Seicean, Andrada; Iuga, Cristina; Seicean, Radu (Cellular and Molecular Biology, 2021)
Current genetic characterization of pancreatic ductal adenocarcinoma (PDAC) does not integrate the host reaction to cancer cells and cannot predict the response to chemo- or immunotherapy. The JAK/STAT pathway is an important factor of cytokine-mediated cancer inflammation, but its relationship with pancreatic carcinogenesis and the role of potential biomarkers is not established yet. Our study aimed to assess the significance of serum levels of JAK/STAT3 expression and inflammatory cytokines in PDAC in relation to the clinicopathological features and prognosis. This prospective cohort study included patients with proven adenocarcinoma and a matched group of controls without any malignancies. There were evaluated the serum expression of IL2, 6, 8, 17, JAK2, and STAT3 by ELISA assays in these two groups. The PDAC patients were followed up for 24 months. A Cox regression multivariate analysis model was used to determine factors influencing survival. The study comprised 56 patients with PDAC and 56 controls. The upregulated serum JAK2/STAT3 or cytokines were present in about half of the patients with PDAC, similar to controls. The expression of JAK2 in serum of PDAC patients was significantly associated with the expression of IL2 (p=0.03) and IL6 (p=0.02) but not with survival or metastasis development. Only age and the presence of lymph node metastases were associated with reduced survival in multivariate analyses. The STAT 3/JAK2 expression, although correlated with inflammatory status (IL2, IL6) was not overexpressed in PDAC compared to controls and proved no prognostic value.